2020
DOI: 10.1002/mus.26854
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit number index in quantitatively assessing motor root lesions and monitoring treatment outcomes in patients with lumbosacral radiculopathy

Abstract: Introduction:We investigated the feasibility of motor unit number index (MUNIX) in quantitatively assessing motor root lesions and tracking different treatment outcomes in lumbosacral radiculopathy (LR).Methods: Bilateral MUNIX was recorded from the abductor hallucis, extensor digitorum brevis, and tibialis anterior in 44 normal controls and 108 patients with LR, and this was repeated approximately 12 months after treatment in 60 patients with LR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…These are increasing evidences that in ammatory stimulation presented with greater correlation with the radicular pain compared to the mechanical stimulation [1,2,[16][17][18]. Although in ammatory substances in the blood sample are similar between two patient groups in this study, the patients undergoing PTED presented with obviously fewer in ammatory substances in the drainage uid than those in the open discectomy patient group.…”
Section: Discussionmentioning
confidence: 44%
“…These are increasing evidences that in ammatory stimulation presented with greater correlation with the radicular pain compared to the mechanical stimulation [1,2,[16][17][18]. Although in ammatory substances in the blood sample are similar between two patient groups in this study, the patients undergoing PTED presented with obviously fewer in ammatory substances in the drainage uid than those in the open discectomy patient group.…”
Section: Discussionmentioning
confidence: 44%
“…These are increasing evidences that in ammatory stimulation presented with greater correlation with the radicular pain compared to the mechanical stimulation [1,2,[18][19][20]. Although in ammatory substances in the blood sample are similar between two patient groups in this study, the patients undergoing PTED presented with obviously fewer in ammatory substances in the drainage uid than those in the open discectomy patient group.…”
Section: Discussionmentioning
confidence: 44%
“…Lumbar disc herniation (LDH) is a degenerative pathology, and it was estimated that approximately 70-80% of the adult population will be affected by this disease during their lifetime [1,2]. Lumbosacral radiculopathy caused by LDH always carries a series of signs and symptoms and often leads to surgical intervention when conservative management fails [2][3][4]. Traditional open discectomy through unilateral interlaminar approach has obtained satisfactory results [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Motor unit number index (MUNIX) is a recently developed quantitative method that provides an estimated index of the number and size of the functional motor units in the tested muscle [8]. According to the previous studies, MUNIX was demonstrated to be very sensitive in detecting motor unit loss in many different neuromuscular diseases [8][9][10][11], and both Li et al and Marciniak et al demonstrated MUNIX detection can be used to assess the integrity of lower motor neuron in patients with SCI [12,13].…”
Section: Introductionmentioning
confidence: 99%